Formerly Incarcerated Black Mothers Matter Too: Resisting Social Constructions of Motherhood. (September 2019) - Mitchell, Michael B.; Davis, Jaya B.
Mass incarceration as a system of racialized and gendered social control has disproportionately impacted Black women, many of whom are mothers. Contrary to dominant social constructions of motherhood, these women employ their own strategies of mothering unique to their lived experiences. This study relies on interview data to understand Black women's motherhood experiences post-incarceration. Drawing from five semistructured interviews of Black mothers across a large urban area in Texas, we argue for more critical, qualitative research of formerly incarcerated Black women, grounded in Black feminist theory (BFT).